Cerebrospinal Fluid P-Tau181P: Biomarker for Improved Differential Dementia Diagnosis - Struyfs, Hanne; Niemantsverdriet, Ellis; Goossens, Joery; Fransen, Erik; Martin, Jean-Jacques; De Deyn, Peter P.; Engelborghs, Sebastiaan (Frontiers in Neurology, 2015)
The goal of this study is to investigate the value of tau phosphorylated at threonine 181 (P-tau181P) in the Alzheimer’s disease (AD) cerebrospinal fluid (CSF) biomarker panel for differential dementia diagnosis in autopsy confirmed AD and non-AD patients. The study population consisted of 140 autopsy confirmed AD and 77 autopsy confirmed non-AD dementia patients. CSF concentrations of Aβ1-42, T-tau, and P-tau181P were determined with single analyte ELISA-kits (INNOTEST®, Fujirebio, Ghent, Belgium). Diagnostic accuracy was assessed through receiver operating characteristic (ROC) curve analyses to obtain area under the curve (AUC) values and to define optimal cutoff values to discriminate AD from pooled and individual non-AD groups. ROC curve analyses were only performed on biomarkers and ratios that differed significantly between the groups. Pairwise comparison of AUC values was performed by means of DeLong tests. The Aβ1-42/P-tau181P ratio (AUC=0.770) performed significantly better than Aβ1-42 (AUC=0.677, P=0.004), T-tau (AUC=0.592, P<0.001), and Aβ1-42/T-tau (AUC=0.678, P=0.001), while P-tau181P (AUC=0.720) performed significantly better than T-tau (AUC=0.592, P<0.001) to discriminate between AD and the pooled non-AD group. When comparing AD and the individual non-AD diagnoses, Aβ1-42/P-tau181P (AUC=0.894) discriminated AD from frontotemporal dementia significantly better than Aβ1-42 (AUC=0.776, P=0.020) and T-tau (AUC=0.746, P=0.004), while P-tau181P/T-tau (AUC=0.958) significantly improved the differentiation between AD and Creutzfeldt-Jakob disease as compared to Aβ1-42 (AUC=0.688, P=0.004), T-tau (AUC=0.874, P=0.040), and Aβ1-42/P-tau181P (AUC=0.760, P=0.003). In conclusion, this study demonstrates P-tau181P is an essential component of the AD CSF biomarker panel and combined assessment of Aβ1-42, T-tau, and P-tau181P renders, to present date, the highest diagnostic power to discriminate between AD and non-AD dementias.